Magnetic Properties of Asteroid (162173) Ryugu. Issue 1 (9th January 2020) - Hercik, David; Auster, Hans‐Ulrich; Constantinescu, Dragos; Blum, Jürgen; Fornaçon, Karl‐Heinz; Fujimoto, Masaki; Gebauer, Kathrin; Grundmann, Jan‐Thimo; Güttler, Carsten; Hillenmaier, Olaf; Ho, Tra‐Mi; Hördt, Andreas; et al.
Abstract: Observations of the magnetization state of asteroids indicate diverse properties. Values between 1.9  ×  10 − 6 Am 2 /kg (Eros) and 10 − 2 Am 2 /kg (Braille) have been reported. A more detailed understanding of asteroidal magnetic properties allows far‐reaching conclusions of the magnetization mechanism as well as the strength of the magnetic field of the solar system regions the asteroid formed in. The Hayabusa2 mission with its lander Mobile Asteroid Surface Scout is equipped with a magnetometer experiment, MasMag. MasMag is a state‐of‐the‐art three‐axis fluxgate magnetometer, successfully operated also on Philae, the Rosetta mission lander. MasMag has enabled, after Eros for the second time ever, to determine the magnetic field of an asteroid during descent and on‐surface operations. The new observations show that Ryugu, a low‐albedo C‐type asteroid, has no detectable global magnetization, and any local magnetization is either small ( < 1 0 − 6  Am 2 /kg) or on very small (subcentimeter) scales. This implies, for example, that energetic solar wind particles could reach and alter the surface unimpeded by strong asteroidal magnetic fields, such as minimagnetospheres in case of the Moon. Plain Language Summary: Magnetic measurements in space near and on solar system bodies such as asteroids can provide important information about their formation history and their material properties. Hayabusa2, a Japanese mission, visited asteroid Ryugu, a type of asteroid (carbon rich) not visited before. Ryugu is a rubble pile, that is, an agglomeration of rocks and boulders. It is not expected to have any global magnetic field, but it can be magnetized on smaller scales (boulders or pebbles). Hayabusa2 carried therefore a small lander called Mobile Asteroid Surface Scout equipped also with an instrument for magnetic field measurement (magnetometer). In this study, we present observations from the magnetometer that were collected during Mobile Asteroid Surface Scout's descent and landing on the surface of Ryugu. The magnetic measurements show that Ryugu is not magnetized on boulder (greater than centimeter) scales. This gives us indication on its origin and evolution. In particular, it shows that Ryugu and the bodies it was created from did not possess any magnetic field generation mechanism and that they were not created in an environment with strong background magnetic field. The results are important inputs for theories about the solar system evolution that work with magnetic field as one of the drivers for dust accretion and planetary formation. Key Points: The study reveals magnetic measurements of a C‐type asteroid Ryugu during landing of MASCOT, the Hayabusa2 lander Observations show no global magnetic moment consistent with Ryugu being a rubblepile asteroid Local magnetization down to centimeter scales is also not detected, indicating nonmagnetic material or magnetization on lower scales